The Influence of Atmosphere, Price, and Service Quality towards Customer Loyalty at Koral Restaurant of Apurva Kempinski, Bali - Angelia Djingga; Angeline Roosaris; Bernardine Inggrid Dakhi; Clarence Chenvona; Gabriella; Vicky Florent (International Journal of Economics, Business Management and Accounting (IJEBMA), 2020)
The abstract of "The Influence of Atmosphere, Price, and Service Quality towards Customer Loyalty at Koral Restaurant of Apurva Kempinski, Bali" outlines a study that examines the relationships between atmosphere, price, service quality, and customer loyalty at the Koral Restaurant of Apurva Kempinski in Bali. Using a quantitative research approach, data was collected through surveys distributed to restaurant patrons. The study employed validated scales to measure the perceived atmosphere, price perception, service quality, and customer loyalty intentions. The collected data was subjected to statistical analysis, including regression analysis, to assess the impact of these factors on customer loyalty. Ethical considerations were observed throughout the research process. The findings contribute to a deeper understanding of the factors influencing customer loyalty in the context of fine dining restaurants, though potential limitations may arise from sample representativeness and self-reported data. Nonetheless, the study offers valuable insights for restaurant management seeking to enhance customer loyalty and overall dining experiences